Use of Sphingomonas yunannensis to Improve Soil Drought Stress in Chili Plants - Andi Febrianti Ramadhani Sri Astuti; Rahayu Widyastuti; Sri Malahayati Yusuf (Jurnal Ilmu Pertanian Indonesia, 2025)
The availability of water plays an important role in plant growth. However, water availability depends on the climate and irrigation channels; therefore, there is little water available for plants during the dry season. Bacteria found in soil can produce exopolysaccharides to survive under extreme land conditions, namely, during drought conditions. The research objectives were to (1) isolate and select bacteria originating from dry land for use on chili plants and (2) determine the effect of water supply frequency and select soil bacteria on chili plants. The experiment consisted of two stages. (1) Bacterial selection and characteristics, which included exopolysaccharide bacteria selection on specific ATCC No. media. 14; pathogenicity test (hypersensitivity and hemolysis); characterization and biochemical testing including pH, temperature, salinity, oxidation, and catalase; bacterial functional tests (P and K solvents and nitrogen-fixing); and (2) tests of chili plants in the greenhouse. The treatment consisted of two factors: (a) application of selected bacteria, (b) frequency of water application (every 1, 2, 3, and 5 days), and (3) molecular identification of selected bacteria. The results showed that the best growth of chili plants was obtained by treating them with bacteria and watering them every other day. Molecular identification demonstrated that the selected bacteria was Sphingomonas yunannensis, which can grow under environmental conditions affected by drought. Keywords: exopolysaccharides, drought, Sphingomonas yunannensis, chili plants